Emotional detachment in psychopathy: Involvement of dorsal default-mode connections. (January 2015) - Sethi, Arjun; Gregory, Sarah; Dell'Acqua, Flavio; Periche Thomas, Eva; Simmons, Andy; Murphy, Declan G.M.; Hodgins, Sheilagh; Blackwood, Nigel J.; Craig, Michael C.
Abstract: Criminal psychopathy is defined by emotional detachment [Psychopathy Checklist – Revised (PCL-R) factor 1], and antisocial behaviour (PCL-R factor 2). Previous work has associated antisocial behaviour in psychopathy with abnormalities in a ventral temporo-amygdala-orbitofrontal network. However, little is known of the neural correlates of emotional detachment. Imaging studies have indicated that the 'default-mode network' (DMN), and in particular its dorsomedial (medial prefrontal – posterior cingulate) component, contributes to affective and social processing in healthy individuals. Furthermore, recent work suggests that this network may be implicated in psychopathy. However, no research has examined the relationship between psychopathy, emotional detachment, and the white matter underpinning the DMN. We therefore used diffusion tensor imaging (DTI) tractography in 13 offenders with psychopathy and 13 non-offenders to investigate the relationship between emotional detachment and the microstructure of white matter connections within the DMN. These included the dorsal cingulum (containing the medial prefrontal – posterior cingulate connections of the DMN), and the ventral cingulum (containing the posterior cingulate – medial temporal connections of the DMN). We found that fractional anisotropy (FA) was reduced in the left dorsal cingulum in the psychopathy group ( p  = .024). Moreover, within this group, emotional detachment was negatively correlated with FA in this tract portion bilaterally (left: r  = −.61, p  = .026; right: r  = −.62, p  = .023). These results suggest the importance of the dorsal DMN in the emotional detachment observed in individuals with psychopathy. We propose a 'dual-network' model of white matter abnormalities in the disorder, which incorporates these with previous findings.